2021
DOI: 10.1108/jiabr-08-2020-0261
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Islamic financial literacy through community-based workshops: a transtheoretical model

Abstract: Purpose This study aims to propose a comprehensive education model to enhance Islamic financial literacy to elevate the prominence of Islamic finance. Design/methodology/approach The study conceptualized a framework of Islamic finance education using Prochaska and DiClemente’s transtheoretical model (TTM) of change aided by a review of the essential literature on Islamic financial literacy. The study also includes critical reflection based on the real firsthand experiences of delivering 16 voluntary non-form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The primary difference between IFL and conventional financial literacy is that Islamic law prohibits interest in financial dealings. Dewi and Ferdian (2021) mention that Islamic law sets the boundary of financial dealings with more permissibilities than prohibitions. The three fundamental prohibitions of Islamic law are: (1) the prohibition of interest, (2) the prohibition of uncertainty and ambiguity in contracts, and (3) the prohibition of unfairness in contracts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary difference between IFL and conventional financial literacy is that Islamic law prohibits interest in financial dealings. Dewi and Ferdian (2021) mention that Islamic law sets the boundary of financial dealings with more permissibilities than prohibitions. The three fundamental prohibitions of Islamic law are: (1) the prohibition of interest, (2) the prohibition of uncertainty and ambiguity in contracts, and (3) the prohibition of unfairness in contracts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While a number of studies have been conducted on IFL but most of them discussed IFL in a generic perspective (Antara et al, 2016; Dewi & Ferdian, 2021; Dinc et al, 2021; Sari et al, 2022). Most of the studies defined IFL as the knowledge of Islamic banking products and services and measured the level of IFL among the people.…”
Section: Introductionmentioning
confidence: 99%
“…So that Muslims have their own terms in defining Islamic financial literacy as a Muslim's understanding of finance, both acceptance of the origin of money and management attitudes in accordance with Islamic teachings (Dewi & Ferdian, 2021). Awlaqi and Aamer (2022) in their research wrote the definition of Islamic financial literacy as knowledge and awareness in Islamic finance so as to base financial decisions based on the Al-Quran and Hadith (Al-Awlaqi & Aamer, 2022a).…”
Section: Literature Review Sharia Financial Literacymentioning
confidence: 99%
“…In prior studies carried out during the 1990s, considerable research on FL has focused on individual understanding of financial concepts. Numerous studies found that FL has a relationship with multi-variables of FL and also assists policy-makers in developing strategies to increase FL in society (Dewi and Ferdian, 2021). Financial awareness and experience positively affect subjective FK and financial skills (Mc Gregor, 2021).…”
Section: Introductionmentioning
confidence: 99%